Intercellular Adhesion Molecule-1 Gene Polymorphisms and Susceptibility to Cervical Cancer in the Northern Chinese Han Population - Feng, Yanan; Li, Xiaoying; Ma, Qi; Zhang, Shuang; Zhu, Manning; Li, Songxue; Fang, Lei; Tian, Jiawei; Sun, Litao (Frontiers in Genetics, 2021)
Many epidemiological studies have confirmed that ICAM-1 gene single nucleotide polymorphisms (SNPs) are associated with various cancers susceptibility, but there are relatively few studies on the relationship between ICAM-1 gene polymorphisms and the risk of cervical cancer. Therefore, we aimed to explore the potential role of ICAM-1 gene polymorphisms and the combined effect of SNPs in the pathogenesis of cervical cancer in Han women in northern China. This case-control group includes 488 cases of cervical cancer, 684 cases of cervical precancerous lesions, and 510 healthy females. Multiplex polymerase chain reaction (PCR) combined with next-generation sequencing method was used for determination of gene polymorphisms (rs5498, rs3093030 and rs281432). In our study, we divide cervical cancer into two subgroups: cervical squamous cell carcinoma (CSCC) group and cervical adenocarcinoma (CAC) group. We analyzed alleles and genotypes of all research subjects using multivariate logistic regression analysis combined with 10,000 permutation tests. In addition, we also analyzed the distribution of haplotypes of the three SNPs in cervical cancer and cervical precancerous lesions. We found that the T allele and the dominant model of rs3093030 was associated with the susceptibility of cervical cancer (p = 0.042, p = 0.040, respectively). However, the significance disappeared after the Bonferroni correction for multiple testing (p > 0.05). For rs5498, its mutant gene G, the codominant model and dominant model could reduce the risk of CAC (p = 0.009, p = 0.028, p = 0.011, respectively). Significant differences remained after Bonferroni correction (p < 0.05, all ). In addition, the frequency of haplotype "CTG" was significantly lower in the CAC group than in the controls. In conclusion, the study suggested that ICAM-1 gene polymorphisms may have a potential role in the pathogenesis of cervical cancer in the northern Chinese han population.